Effect of strain and nonparabolicity on interband transition energies of InAs/GaAs coupled double quantum dots - Kwon, Hye Young; Woo, Jun Taek; Lee, Dea Uk; Kim, Tae Whan; Park, Young Ju (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Strained potential profiles and electronic subband energies of InAs/GaAs coupled double quantum dots (DQDs) were calculated by using a three-dimensional finite-difference method (FDM) taking into account shape-based strain and nonparabolic effects. The interband transition energies from the ground electronic subband to the ground heavy-hole band (E-1-HH1) in the InAs/GaAs DQDs, as determined from the FDM calculations taking into account strain and nonparabolic effects, were in reasonable agreement with the experimental peaks corresponding to the (E-1-HH1) interband transition energies at several temperatures, as determined from the temperature-dependent photoluminescence spectra. (C) 2008 Published by Elsevier Ltd